PRODUKSI FILM BIOMULSA DARI KLOBOT JAGUNG - LLDPE UNTUK APLIKASI DI BIDANG HORTIKULTURA - Mersi Kurniati, Akhiruddin Maddu, dan Sidikrubadi Pramudito (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
From a crop production perspective, plastic mulches can increase yields, extend the growing season, reduce weed pressure, increase fertilizer use efficiency, conserve soil moisture, and increase soil temperature. A major limitation of polyethylene mulch involves disposal of mulch material following use. Recently, biodegradable mulch films have been viewed as a more sustainable ecological alternative to plastic polyethylene mulch. In an effort to cope up with the severe and continuously growing agricultural plastic waste problem, biodegradable film was fabricate using natural waste (corn husk) as reinforcing agent and the film fabricated was used to produce biodegradable mulching fim (Biomulch). In this research, the biomulch of the corn husk and Linear Low Density Polyethylene (LLDPE) produced by extrusion and calandering method with a width of 25 cm has been made. Biomulches were made of corn husksby concentration of: 5, 10 and 15% (% w/w). Proximate and fiber analysis were conducted to determine the composition of corn husks. The biomulches were produced were analyzed by mechanical, thermal, microstructure, morphological, and functional group properties.The results showed that the mechanical characteristics decreased with the addition of cornhusk concentration on biomulches, and concentration 5 % had the highest mechanical characteristics with tensile strength of 14.52 MPa, elongation at break of 358.10% and modulus of elasticity of 0.37 GPa. Keywords: biomulches, corn husks, calandering, LLDPE